The dis-closure of "Huckleberry Finn:. Natura naturata vs. lumen naturale, lighting out vs. Lichtung - Semrau, Janusz (Adam Mickiewicz University, 2007)
Against the popular frontier-wilderness discourse, the paper offers to discuss one of the most celebrated lines in all American literature, Huck Finn’s closing resolution to light out ahead of the rest, as an adverbial-existential rather than as a categorical-territorial affair. Drawing on Heidegger’s notion of “resoluteness”, it is argued that the novel discloses at the very end – ‘lights out’ – a mode of presencing rather than of disappearing. More broadly, this is to show that the received image of Huck as a maverick dodger, incorrigible vagabond and, most emphatically of all, as a celebrant of Nature is not borne out by the reality of the text and is informed instead by the dynamics of cultural (auto-)stereotyping.